Axial anomaly through analytic regularization - Manzoni, L. A. [UNESP]; Pimentel, B. M. [UNESP]; Tomazelli, J. L. [UNESP] (My University, 1999)
In this work we consider the two-point Green's functions in (1 + 1)-dimensional quantum electrodynamics and show that the correct implementation of analytic regularization gives a gauge invariant result for the vacuum polarization amplitude and the correct coefficient for the axial anomaly.